ANALISIS PENERAPAN AKUNTANSI PAJAK PENGHASILAN PASAL 21 ATAS GAJI PEGAWAI NEGERI SIPIL PADA BADAN PENANGGULANGAN BENCANA DAERAH KOTA BINJAI - Tinambunan, Herdina Br; Sirait, Devi Ayu Putri; pane, Aditya Amanda (Gapenas Publisher, 2025)
This study aims to analyze the implementation of income tax accounting article 21 on civil servants’ salaries at the Regional Disaster Management Agency (BPBD) of Binjai City. Income tax article 21 is a tax imposed on income in the form of salaries, wages, honorariums, allowances, and other payments received by employees. Problems often arise due to discrepancies between calculation, recording, and reporting of article 21 income tax with applicable tax regulations. The research method used is descriptive qualitative with a case study approach at BPBD Binjai City, employing interviews, observations, and documentation techniques. The results show that the implementation of article 21 income tax accounting at BPBD Binjai has been carried out in accordance with tax regulations, although there are still obstacles related to reporting delays and administrative errors. This study recommends that PPh 21 management be more systematic by utilizing tax applications and improving staff competence. This research is expected to contribute to tax literature, especially in the public sector, and become a consideration for local government agencies in improving compliance and effectiveness in managing employee income tax.